2021
DOI: 10.1186/s13717-021-00298-1
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of bird communities following the construction of a large-scale hydroelectric dam

Abstract: Background Habitat degradation is known to have a major impact on the composition of bird communities, yet how these communities recover following such disturbance is less understood. This study examined bird community changes from pre-logging to recovery over the course of habitat disturbance caused by the development of the Hulu Terengganu Hydroelectric Dam Project in Peninsular Malaysia, between 2007 and 2018. Bird surveys were conducted using point count observations and mist netting in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The granivore bird group prefers open areas with low vegetation density (Rofiq et al 2021). In addition, it is observed that the granivore group has a response to increasing the number of groups after logging or loss of trees in a habitat and decreases while there is regrowth during the recovery period to a more complex forest (Burivalova et al 2015;Nasruddin-Roshidi et al 2021). Therefore, the presence of high G guilds in a specific area can indicate that the area has a low density of high-level vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…The granivore bird group prefers open areas with low vegetation density (Rofiq et al 2021). In addition, it is observed that the granivore group has a response to increasing the number of groups after logging or loss of trees in a habitat and decreases while there is regrowth during the recovery period to a more complex forest (Burivalova et al 2015;Nasruddin-Roshidi et al 2021). Therefore, the presence of high G guilds in a specific area can indicate that the area has a low density of high-level vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Birds are the ideal subjects to study the effects of habitat fragmentation and landscape change as they are easily identified, clearly visible and sensitive to land-use changes (Hensley, 2018;Mansor et al, 2011;Nasruddin-Roshidi et al, 2021). Birds are also often clearly visible to the public in the city, and their presence is highly anticipated by most visitors to urban parks (Jasmani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%